Efektifitas Program LIFE (Literacy Initiative For Empowerment) UNESCO Dalam Meningkatkan Human Development Index Republik Niger Tahun 2006–2015 - Pradika, Oktavia Rizki (Global and Policy Journal of International Relations, 2017)
ABSTRACTThe Literacy Initiative For Empowerment (LIFE) is a UNESCO framework set up to help increase literacy rates in 35 countries. The LIFE framework was born to achieve some of the goals set out in EFA (Education For All), Dakar in 2000. Dakar Goals 3 on meeting the learning needs of young and mature people, Dakar Goals 4 refers to an increase in adult literacy rates by up to 50% , and Dakar Goals 5 that fought for equal rights between men and women in education. Using concepts and theories about social welfare in the context of development of the state and human resources, this study focuses on proving the effectiveness of LIFE in enhancing human development of the Republic of Niger. Through explanative research method, this research yields data finding that LIFE framework is considered effective in improving human development index. Human development index is used to measure the quality of human resources ranging from knowledge through the level of literacy, life expectancy through population ratio, and quality of life standards that can be measured through GNI or income per capita.Keywords: LIFE, Republic of Niger, Literacy, Human DevelopmentDOI: https://doi.org/10.33005/jgp.v5i02.1891